Tourism and religious heritage in the city of Kadhimiya And his role in solving Iraqi social and political problems - Easa, Ahlam Ahmad (Al-Adab Journal, 2019)
Religious Heritage one of the tributaries of Iraq's economy as it includes the land of Iraq, particularly the city of Baghdad, the study area lands fertile and abundant water and Ishqh Tigris and Euphrates rivers and other sources such as lakes and archaeological sites and cultural addition to the holy shrines and religious shrines for Muslims and other sects which represents the city of Kadhimiya important aspect for Muslims frequented by tourists from all countries of the world and in all seasons of the year where the sacred Kadhimiya of kindergarten Kadhimiya Immaculate contain shrine (Musa Kadhim and Mohammed Jawad), peace be upon them, and Bjawarmedinh sacred Kadhimiya surrounding areas that have religious significance collector and the shrine of Sheikh Abdul Kader al-Kilani, and a mosque and shrine of Imam Abu Hanifa and that's what drives us towards tourism growth and development of the holy city of Kadhimiya, because development help to increase investment and development of the Iraqi economy opportunities and thereby increase economic and social benefits and assess the cultural and civilizational and religious heritage through the growing number of tourists to the city of Kadhimiya holy that's what happens through the development of the tourism sector (religious tourism) because development lead to the distribution of the fruits of development to the members of the community as part of a tourism fair and equitable also helps in the management cons of tourism, reduce and determine the effects control, but providing elements of development and is certain that Iraq and the city of Kadhimiya rich areas of tourist attractions, where available the most important aspect of development which the elements of internal and external tourism inside the holy city of Kadhimiya, but the circumstances experienced by Iraq for more than four centuries have been instrumental in weakening the chances that a sophisticated tourism industry and the establishment of a modern tourist service facilities although issued by the introduction Mohlh Arab countries to attract tourism to the millions of tourists every year and thus achieve tourism development through the development of small shrines and religious buildings and improve the surrounding areas and the development of the role of tourism information through the development of programs for television channels to promote